A systematic review of the clinical evidence and biomarkers linking allergy to adeno-tonsillar disease. (August 2021) - De Corso, Eugenio; Galli, Jacopo; Di Cesare, Tiziana; Lucidi, Daniela; Ottaviano, Giancarlo; Seccia, Veronica; Bussu, Francesco; Passali, Giulio Cesare; Paludetti, Gaetano; Cantone, Elena
Abstract: Introduction: allergy may be an important risk factor for adenotonsillar disease in children, although conflicting results have been reported in the literature. In previous articles, authors often failed in distinguishing between adeno-tonsillar hypertrophy and recurrent tonsillitis and in not discriminating between isolated or combined adenoid and tonsillar hypertrophy. Aim: to evaluate clinical evidence and biomarkers linking allergy to different phenotypes of adeno-tonsillar disease. Furthermore, we questioned whether anti-allergy treatment might prevent occurrence of adeno-tonsillar disease or improve its specific management. Methods: our systematic review, in accordance with the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) process, yielded 1010 articles finally screened. This resulted in 21 full texts that were included in a qualitative analysis. Results: literature data support the association between allergy and combined adeno-tonsillar hypertrophy and isolated adenoid hypertrophy, whereas describe a mainly negative correlation between allergy and isolated tonsillar hypertrophy. The results of this review suggest that local allergic inflammation may play a role in adeno-tonsillar hypertrophy. Data correlating bacterial recurrent tonsillitis and allergy are few, although evidence from the lab revealed that allergy might suppress innate immunity in tonsillar tissue by reducing levels of anti-microbial proteins. Conclusion: basing on our qualitative analyses allergy should not be misdiagnosed in children with combined adenotonsillar hypertrophy or isolated adenoid hypertrophy, whereas evidence do not support a link between allergy and isolated tonsil hypertrophy. Finally, some data support a link between allergy and recurrent adeno-tonsillar infection although future studies are required to confirm this data. We summarized our conclusions in a practical algorithm.